Symptomatic hypersomnia due to orexin deficiency in hypothalamic lesions - Kanbayashi, Takashi; Arii, Junko; Kubota, Hiroaki; Yano, Tamami; Kashiwagi, Mitsuru; Yoshikawa, Sousuke; Tohyama, Jun; Sawaishi, Yukio (No to hattatsu, 2006)
Narcolepsy is characterized by excessive daytime sleepiness (EDS), cataplexy and other abnormal manifestations of REM sleep. Recently, it was discovered that the pathophysiology of idiopathic narcolepsy-cataplexy is linked to orexin ligand deficiency in the brain and cerebrospinal fluid. Orexin neurons localize in the posterior hypothalamic area, which was previously described as "waking center" by von Economo in 1920s. Hypersomnia due to orexin ligand deficiency can also occur during the course of other neurological conditions, such as hypothalamic tumor, encephalopathy and demyelinating disorder (i.e. symptomatic hypersomnia). We experienced 8 pediatric cases with symptomatic hypersomnia. These cases were diagnosed as brain tumor (n = 2), head trauma (n = 1), encephalopathy (n = 1), demyelinating disorder (n = 3) and infarction (n = 1). Six pediatric cases with orexin measurements from the literatures were additionally included and total 14 cases were studied. Although it is difficult to rule out the comorbidity of idiopathic narcolepsy in some cases, a review of the case histories reveals numerous unquestionable cases of symptomatic hypersomnia. In these cases, the occurrences of the hypersomnia run parallel with the rise and fall of the causative diseases. Most of symptomatic hypersomnia cases show both extended nocturnal sleep time and EDS consisting of prolonged sleep episodes of NREM sleep. The features of nocturnal sleep and EDS in symptomatic hypersomnia are more similar to idiopathic hypersomnia than to narcolepsy.